Informe técnico campo de acción institucional -cai-. espacio y territorio (2002)
The necessity to raise a series of Theoretical - Methodological items for the handling of thematic of space and territory by University is contemplated in the Global Plan of Development of the National University of Colombia 1999- 2003: An Academic and Social Commitment with the Colombian Nation. The directives drawn up in this document aim at the University to afirm itself as an Institution able to assume their «academic and social commitment with the Colombian Nation» by means of the useful construction of knowlege for the interpretation and solution of diverse problems that the Colombians face. For such effect, the plan has settled down that the activities of the University must be inserted in the strategies for the fortification of the following aspects: National Presence, Internationalization, Quality and Academic Property, Efficient Management and Fairness, and Coexistence.